Herbaria of the Prussian physician Boretius (1694-1738) in the Herbarium WA - Graniszewska, Maja; Kapler, Adam (Biodiversity: Research and Conservation, 2018)
Pre-Linnaean herbaria have a growing value for botanists and historians of science. A unique example is a four volume herbarium from the early 18th century preserved in the archives of the Herbarium of the Faculty of Biology, University of Warsaw. They consist of one, originally five volume set. We proved that the plants had been gathered by the famous naturalist Georg Andreas Helwing (1666-1748), and his son-in-law, Matthias Ernst Boretius (1694-1738), and they annotated and classified the exhibits. Boretius was born in Prussia, in Lec (now: Giżycko). He acquired his academic training in Königsberg and Leiden, and deepened it by scientific travels. He was the first in Masuria to promote vaccination against smallpox. Earning the reputation of a distinguished scholar, he was appointed Royal Physician and Crown Councilor of the Prussian court. He died in 1738 at the age of just 44, leaving the herbarium vivum – a magnificent remnant of his times. There are over 900 cards with glued specimen, signed in three languages: Latin, German and Polish. It includes vascular plants, liverworts, true mosses, clubmosses, algae and macrofungi. Boretius implemented the system made known by the French botanist Joseph Pitton de Tournefort (1656-1708). His system divided the plant world into 22 classes, based on flower morphology but also retaining the traditional split into trees, shrubs and forbs. The choice of this arrangement by Boretius was an innovation; the earlier plant collections of his tutor Helwing lacked any attempt to classify plant species.